2017
DOI: 10.1038/s41598-017-11772-2
|View full text |Cite
|
Sign up to set email alerts
|

Urea deep placement reduces yield-scaled greenhouse gas (CH4 and N2O) and NO emissions from a ground cover rice production system

Abstract: Ground cover rice production system (GCRPS), i.e., paddy soils being covered by thin plastic films with soil moisture being maintained nearly saturated status, is a promising technology as increased yields are achieved with less irrigation water. However, increased soil aeration and temperature under GCRPS may cause pollution swapping in greenhouse gas (GHG) from CH4 to N2O emissions. A 2-year experiment was performed, taking traditional rice cultivation as a reference, to assess the impacts of N-fertilizer pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 46 publications
3
15
0
Order By: Relevance
“…Aside from the differences in the water regimes between the abovementioned studies on rice cultivation and the results presented here, the definition of what is considered a deep placement is quite relative and varies between studies. For example, Schutz et al (1989) and Yao et al (2017) studied a placement depth of 0.20 and 0.10-0.15 m, respectively, which is comparable to the DP treament presented in this study. By contrast, Rath et al (1999) considered 0.05 m to be a deep placement, which is analogous to our SP treatment.…”
Section: Effect Of N Placement On Ch 4 Emissionssupporting
confidence: 56%
“…Aside from the differences in the water regimes between the abovementioned studies on rice cultivation and the results presented here, the definition of what is considered a deep placement is quite relative and varies between studies. For example, Schutz et al (1989) and Yao et al (2017) studied a placement depth of 0.20 and 0.10-0.15 m, respectively, which is comparable to the DP treament presented in this study. By contrast, Rath et al (1999) considered 0.05 m to be a deep placement, which is analogous to our SP treatment.…”
Section: Effect Of N Placement On Ch 4 Emissionssupporting
confidence: 56%
“…Nevertheless, the incorporation of N fertilizer in the deeper soil layers also stimulated N 2 O production from nitrification–denitrification processes compared with the control plots (Figure ). Water saturation in soils slows or even prevents the diffusion of N 2 O produced in deeper soil layers (Yao et al, ), which might lead to the further reduction of N 2 O to N 2 prior to its release to the atmosphere (Butterbach‐Bahl et al, ; Davidson, Keller, Erickson, Verchot, & Veldkamp, ).…”
Section: Discussionmentioning
confidence: 99%
“…A meta‐analysis conducted by Xia, Lam, et al () demonstrated that the incorporation of N fertilizer into the soil significantly decreased the emission of NH 3 from paddy fields by 26.4% and increased the yield of rice by 7.0%. Yao et al () reported that using a slow‐release urea fertilizer incorporated into the soil decreased N 2 O emissions from paddy fields by 40.9%–56.8%.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, integrating the findings of ECO2 effects on N 2 O (this study) and CH 4 (Zheng et al., 2006) shows that total non‐CO 2 GHG emissions from rice systems will rise with increasing atmospheric CO 2 , but that the ECO2‐induced reductions in soil N 2 O emissions negate as much as 24% of the increases in soil CH 4 emissions. However, this increase in non‐CO 2 GHG emissions from rice systems under ECO2 can be significantly reduced by improving water regimes and using alternative fertilization practices such as alternate wetting and drying irrigation schemes, ground cover rice production system and urea deep placement (Beach et al., 2008; Linquist et al., 2015; Yao, Zheng, Liu, et al, 2017; Yao, Zheng, Zhang, et al, 2017). Also, adopting rice cultivars with potentially strong responses to ECO2 may eventually not only improve crop yield but also enhance soil C sequestration (Hu et al., 2020), thereby curbing the future growth of greenhouse effect contributed by rice systems.…”
Section: Discussionmentioning
confidence: 99%